Ghostly Visitations in Contemporary Short Fiction by Women: Fay Weldon, Janice Galloway and Ali Smith - Sacido-Romero, Jorge (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2016)
From the late nineteenth century onwards the genre of the ghost short story has served as a vehicle for the exploration of female concerns. Women’s ghost narratives feature heroines haunted by spectral apparitions that give expression to the characters’ inner tensions with their assumption of socially sanctioned female roles. This essay reads three stories, by Fay Weldon, Janice Galloway and Ali Smith, to show how the potential of the genre to question the norm and to give shape to personal, intergenerational and historical conflicts continues to be deployed by contemporary women writers. As in the stories of their female predecessors, the effects of the literary ghost’s disturbing liminality vary in each of the cases under consideration here. Thus, the apparition in Weldon’s “A Good Sound Marriage” (1991) works as a contested mouthpiece of traditional sexual ideology, the oneiric revenant in Galloway’s “it was” (1991) is the figuration of unconscious desire, while the doppelgänger in Smith’s “The Hanging Girl” (1999), despite her spectrality, inhabits a less empty and more amiable world than that of real flesh-and-blood people. Keywords: ghost story; short story; women’s writing; Fay Weldon; Janice Galloway; Ali Smith